Using Simulation to Improve Medical Students’ Comfort with Selected Pediatric Procedures - Harrison, Mark E; Kroeker, Deborah A; Ahlers-Schmidt, Carolyn R (Kansas Journal of Medicine, 2015)
BACKGROUND: Simulation in pediatrics is described often in more procedurally-heavy areas, such as in intensive care, emergency medicine, and neonatology. However, there is a paucity of literature related to simulation in general pediatrics. We sought to improve students’ comfort with and knowledge about selected procedures using simulation mannequins during their pediatric rotation. METHODS: During a workshop, third year medical students received a lecture on male circumcisions, lumbar punctures, the Ortolani and Barlow maneuvers, and ear examinations. Following the lecture, the students were given hands-on instruction and feedback on the techniques for performing ear and hip exams, lumbar punctures, and circumcisions. Students took a pre- and post-encounter assessment regarding their confidence level, procedural knowledge, and perceived usefulness of the training. Wilcoxon Signed Rank tests were used to determine changes in the students’ confidence levels and knowledge. Alpha was set at 0.05 for all comparisons. RESULTS: Sixty medical students (100%) participated in the study during the 2012/2013 academic year. Confidence and knowledge increased significantly on all procedures following the simulation experience (p < 0.001). Perception of usefulness of the training also increased significantly at post-test (p = 0.019). CONCLUSION: Medical students benefited from using simulation to demonstrate and practice common pediatric procedures, both in their confidence and knowledge. The use of simulation for general pediatric procedures should improve patient safety, as well as remove some of the anxiety of performing procedures in actual clinical scenarios.